The risk premium channel and long-term growth - Malte Daniel Schumacher; Dawid Żochowski (European Central Bank (ECB), 2017)
We study a quantitative DSGE model linking a state of the art asset pricing framework à la Kung and Schmid (2015) with a constraint on leverage as in Gertler and Kiyotaki (2010). We show that a mere increase in the probability of firms being financially constrained leads to an increase in risk premia. Even for a small adverse shock to productivity a drop in asset valuation restrains firms from outside financing and by that induces a persistent low growth environment. In our framework a constraint on leverage induces countercyclical risk premia in equity markets even when it does not bind.
Keywords: D53; G01; G12; 330; risk premia; financial accelerator; asset pricing; endogenous growth